Aqueous−humor biomarkers and real−world efficacy of conbercept for diabetic macular edema: a prospective study in elderly patients - Xie, Min (Frontiers in Endocrinology, 2025)
BackgroundTo evaluate real−world efficacy of conbercept and the predictive value of aqueous−humor biomarkers in elderly diabetic macular edema (DME).MethodsIn this single−arm, prospective study, 150 patients ≥ 65 years received three monthly conbercept injections followed by pro−re−nata dosing over 6 months. Baseline vascular endothelial growth factor (VEGF) and interleukin−6 (IL−6) levels were quantified from aqueous humor; best−corrected visual acuity (BCVA) and central subfield thickness (CST) were monitored. Mixed−effects modelling and receiver−operating−characteristic (ROC) analysis explored associations between biomarkers and outcomes.ResultsMean BCVA improved by approximately nine ETDRS letters, and CST declined by about 85 µm at Month 6. Higher baseline VEGF and IL−6 were associated with greater CST reduction and moderately increased odds of a ≥ 15−letter gain; VEGF showed fair discriminative ability (AUC=0.74). Treatment was well−tolerated, with no unexpected ocular or systemic adverse events.ConclusionConbercept produced meaningful anatomical and functional benefits in an elderly DME cohort. Baseline aqueous VEGF and IL−6, while not definitive stand−alone tests, may help identify eyes likely to achieve pronounced anatomical improvement and warrant further investigation as components of a multi−marker predictive panel.